2020
DOI: 10.2196/20775
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Korean-Language COVID-19–Related Medical Information on YouTube: Cross-Sectional Infodemiology Study

Abstract: Background In South Korea, the number of coronavirus disease (COVID-19) cases has declined rapidly and much sooner than in other countries. South Korea is one of the most digitalized countries in the world, and YouTube may have served as a rapid delivery mechanism for increasing public awareness of COVID-19. Thus, the platform may have helped the South Korean public fight the spread of the disease. Objective The aim of this study is to compare the relia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
63
3
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 57 publications
9
63
3
5
Order By: Relevance
“…This percentage of useful information was higher than those reported by previous studies (58.3–63%) assessing medical health information on YouTube videos related to hypertension, dialysis, and influenza [ 29 , 31 , 32 ]. In studies that recently analyzed misinformation about COVID-19 on YouTube [ 7 , 18 , 33 ], the percentage of useful videos was also determined to be lower (37.14–72.50%) compared to our study. Concerning rheumatic diseases, YouTube studies have shown varying results; for example, the rate of useful videos was reported as 51.4% for Sjogren’s syndrome [ 1 ] and 54.9% for rheumatoid arthritis [ 5 ], which were both lower than our study, while studies on spondyloarthritis and systemic lupus erythematosus determined similar rates to our study (86% and 83.60%, respectively) [ 8 , 9 ].…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…This percentage of useful information was higher than those reported by previous studies (58.3–63%) assessing medical health information on YouTube videos related to hypertension, dialysis, and influenza [ 29 , 31 , 32 ]. In studies that recently analyzed misinformation about COVID-19 on YouTube [ 7 , 18 , 33 ], the percentage of useful videos was also determined to be lower (37.14–72.50%) compared to our study. Concerning rheumatic diseases, YouTube studies have shown varying results; for example, the rate of useful videos was reported as 51.4% for Sjogren’s syndrome [ 1 ] and 54.9% for rheumatoid arthritis [ 5 ], which were both lower than our study, while studies on spondyloarthritis and systemic lupus erythematosus determined similar rates to our study (86% and 83.60%, respectively) [ 8 , 9 ].…”
Section: Discussioncontrasting
confidence: 70%
“…The videos meeting the inclusion criteria were evaluated in terms of usefulness and categorized as useful and misleading. In accordance with previous studies [ 7 , 20 , 21 ], the videos were considered as useful if they included scientifically accurate information about any aspect of the disease (e.g., symptoms, clinical features, diagnosis, treatment, and prevention) or misleading if they included at least one scientifically unproven information.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results showed that 40% of this information was from unreliable sources [ 22 ]. At the same time, Moon et al [ 39 ] collected 200 of the most viewed Korean-language YouTube videos on COVID-19 published from January 1 to April 30, 2020. They found that 37.14% of the videos contained misinformation, and independent videos generated by the user showed the highest proportion of misinformation at 68.09%, whereas all government-generated videos were regarded as useful.…”
Section: Introductionmentioning
confidence: 99%